Risk-based dynamic generation and transmission expansion planning with propagating effects of contingencies - Mehrtash, Mahdi; Kargarian, Amin (International journal of electrical power & energy systems, 2020)
•A risk-based dynamic generation and transmission expansion planning model is proposed.•The propagating effect of each contingency on the power system is modeled with risk indices.•Post-contingency load-shedding costs are used to penalize high-risk contingencies more dominantly.•The McCormick relaxation is tailored to alter the objective function into a linear format.•A second-order cone programming model is applied for power flow representation. Transmission networks and generating units must be reinforced to satisfy the ever-increasing demand for electricity and to keep power system reliability within an acceptable level. According to the standards, the planned power system must be able to supply demand in the case of outage of a single element (N-1 security criteria), and the possibility of cascading failures must be minimized. In this paper, we propose a risk-based dynamic generation and transmission expansion planning model with respect to the propagating effect of each contingency on the power system. Using the concept of risk, post-contingency load-shedding penalty costs are obtained and added in the objective function to penalize high-risk contingencies more dominantly. The McCormick relaxation is tailored to alter the objective function into a linear format. To keep the practicality of the proposed model, a second-order cone programming model is applied for power flow representation, and the problem is modeled in a dynamic time frame. The proposed model is formulated as a mixed-integer second-order cone programming problem. The numerical studies on the RTS 24-bus test system illustrate the efficacy of the proposed model.